Sejarah Kodifikasi Al-Qur’an (Jam’ul Qur’an) dan Implementasinya dalam Budaya Kedisiplinan Akademik di Sekolah Raudlatul Muta’allimin Lamongan.: Penelitian - Geovany Famwanto; Ahmad Hanif Fahruddin (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The Qur'an represents a fundamental miracle in Islamic doctrine, revealed by Allah SWT to the Prophet Muhammad SAW through the intermediary of Angel Gabriel. This study aims to reconstruct the history of the Qur'an's codification, which transformed from scattered manuscript fragments into a comprehensive and systematic mushaf structure. This writing uses a qualitative methodology with a library research approach. Data is collected through documentation techniques and critical analysis of various literature, scientific articles, and journals relevant to the discourse of Jam’ul Qur’an. Through the examination of these sources, this study seeks to dissect the dynamics of preserving the holy text from historical and administrative perspectives. Research findings indicate that the process of unifying and compiling the Qur'an took place in two crucial periods. The first phase occurred during the prophetic era, where revelations were documented partially on simple media. The second phase was the era of standardization carried out by the Rightly Guided Caliphs. This included the initiation of manuscript collection during the time of Abu Bakr as-Siddiq, prompted by the urgent need due to the loss of many memorizers, the standardization of the script during the time of Uthman ibn Affan to prevent dialectical division, and ongoing maintenance during the time of Ali ibn Abi Talib. In conclusion, the transition from separate sheets to a single mushaf was a strategic effort to preserve the authenticity and integrity of the revelation from the risk of historical distortion and significant differences in reading among Muslims.